PROPOSTA DE METODOLOGIA DE INVESTIGAÇÃO DE INCIDENTES E DESVIOS COMPORTAMENTAIS COMO FERRAMENTA COMPLEMENTAR PARA GESTÃO DE SMS NA IMPLEMENTAÇÃO DE EMPREENDIMENTOS DE ENGENHARIA DA INDÚSTRIA DE PETRÓLEO NO BRASIL. - Santos, Helio Ricardo da Fonseca (2009)
This paper aims to leverage the importance of the research on losses and show the relevance of using a structured methodology as a tool for proactive investigation and handling of incidents and potential deviation to improve the work-focused behavior in Projects of Engineering Oil Industry in Brazil. This view, within the HSE Management, proposes a more effective and deeper with this tool to identify the causes to stay ahead of an undesired event based on the actions implemented from investigations of "near misses" which did not become loss probably through lack of a systemic contributor. Regardless of how important the behavioral focus and is aligned with the objective of improving the results in the pursuit of excellence in HSE, this work also proposes a combination of two structured models of research loss, incidents and high potential deviations. These models have been benchmarked on studies in one of the largest oil companies in Brazil with a management model in place and is still anticipated that the loss for the establishment of their corrective actions, preventive and predictive SMS, demonstrating the contribution of the proposal of this work over the years in an enterprise engineering.